Rola ojca na podstawie 20. homilii Jana Złotoustego na list św. Pawła do Efezjan - Yatskov, Dem’yan (Vox Patrum, 2013)
The division of family responsibilities, which are designed for each household member and harmonious family relationships are one of the most important keynotes of St. John’s Chrysostom preaching. In order to explain this issue he wrote homily on the Epistle to the Ephesians. According to it, the role of father in household is based on following Christ. Husbant’s relationship to his wife, especially respect for her, should be built by analogy to the relationship between Christ and the Church. The author calls the family a “small church”, comparing it to the Church as the Mystical Body. Living of the “small Church” is permeated with prayer and Holy Scripture reading. Firstly husband – the head of the family, performs the following Christian actions: reads inspired texts, strengthens himself by the sacrament of the Eucharist (that is , he takes the Holy Communion). And thanks to that going to church and celebrate the Lord’s Day, are the usual practice of all members of the parva Ecclesia.